The effectiveness of cognitive behavior modification approaches in reducing pornographic behavior in SMAN 1 Sungai Geringging with group setting - Indah Kumala Sari; Yeni Karneli (Universitas Negeri Padang, 2019)
Pornographic behavior is an act where a person witnesses, reads, or hears and talks about a sexual material explicitly, thus causing sexual desire and passion. This study aims to (1) describe pornographic behavior in students at Sungai Geringging 1 High School (2) describe the Cognitive Behavior Modification (CBM) approach to reduce pornographic behavior (3) test the effectiveness of the Cognitive Behavior Modification approach effectively reducing pornographic behavior. This research uses quantitative methods with the type of pre-experimental research with the research design of the one goup pretest posttest design. The research subjects were 10 students of SMAN 1 Sungai Geringging class XI IIS 1. The data collection tool used was a questionnaire. Data analysis techniques used Wilcoxon signed range test design data analysis. The results showed that the Cognitive Behavior Modification approach was effective in reducing pornographic behavior in students with 71.4% pretest results in the high category and 41.1% in the posttest in the low category. This study gives meaning that the Cognitive Behavior Modification approach is able to reduce pornographic behavior in students, for that teachers guidance and counseling need to apply this approach in implementing counseling services.